Right ventricular longitudinal deformation parameters and exercise capacity Prognosis of patients with chronic thromboembolic pulmonary hypertension - KEPEZ, ALPER; ÖZBEN SADIÇ, BESTE; SÜNBÜL, MURAT (URBAN & VOGEL, 2014)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a progressive disease characterized by increased pulmonary vascular resistance resulting in pulmonary hypertension and right heart failure. The six-minute walk test (6MWT) distance is associated with the prognosis of CTEPH patients. Speckle tracking echocardiography (STE) is a reliable method for determining ventricular function. The aim of this study was to assess and compare the right ventricular (RV) function of CTEPH patients according to their 6MWT distances. Forty-nine consecutive CTEPH patients (mean age, 50 +/- 16 years; 22 male) who were referred to our center for pulmonary thromboendarterectomy (PTE) were included in the study. All patients underwent the 6MWT and right heart catheterization (RHC). Standard echocardiography and STE were performed on all patients before PTE. Patients were divided into two groups based on their 6MWT distance being less or more than 300 m. Patients with a shorter 6MWT distance had a significantly larger RV, while they had a significantly lower RV fractional area change and higher myocardial performance index suggesting impaired RV function. Both RV basal-lateral strain and strain rate measures were significantly lower in patients with shorter 6MWT distances than those with longer 6MWT distances. Similarly, they had lower RV basal-septal, mid-lateral, and global strain measures. 6MWT distances were correlated with RV basal-lateral and mid-lateral strain measures (r = 0.349, p = 0.025 and r = 0.415, p = 0.008, respectively). Our data suggest that RV myocardial deformation parameters are associated with 6MWT distances. Determination of RV dysfunction by STE may be helpful in identifying patients with a poor prognosis.
Keywords: Chronic thromboembolic pulmonary hypertension; Right ventricular function; Six-minute walk test; Speckle tracking echocardiography; Thromboendarterectomy; 6-MINUTE WALK TEST; SPECKLE-TRACKING; TISSUE DOPPLER; STRAIN-RATE; ECHOCARDIOGRAPHY; UTILITY